Analysis Of Village Funds On The Implementation Of Development In Layang Lekat Village, Pagar Jati District, Bengkulu Central Regency - Tri Purwanti (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
This research is motivated by One way to realize good governance in managing the Village Fund budget is to pay attention to the stages of management, planning, implementation, reporting, and accountability. In managing the government in a village, the village head needs assistance from the villagers. The people of this village work according to their duties. Because of its large role, it is necessary to formulate regulations or laws related to village government to regulate village government, so that they can carry out their roles as well as possible. In this regard, the role of the community is also important, especially in the decision-making process and the implementation of activities related to the needs of the village community. The purpose of this study was to find out how the implementation of village fund allocation management (ADD) for rural development in Layang Lekat Village, Pagar Jati District, Central Bengkulu Regency. The type in this study was qualitative with descriptive methods, observation data collection techniques, interviews and documentation, after interviews. carried out with selected informants, the researchers used data analysis techniques, namely collecting data, presenting data, drawing conclusions.The results of the study show that the policy of the Layang Lekat Village Head has been implemented properly, the policy of the Layang Lekat Village Head is to organize or manage the village fund budget for the implementation of village development, both physical and non-physical. The process of managing village funds for the implementation of Layang Lekat village development consists of several stages, namely planning, implementation, and accountability reporting. Management of the Layang Lekat Village Fund It has been quite effective in the implementation of the development of the village, the realization of the management of the Village Fund for the implementation of development in the Lekat Layang Village which has been carried out well in 202 to 2021 .